2020
DOI: 10.29261/pakvetj/2020.007
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical Detection of Kisspeptin Receptor and Its Association with Motility of Buffalo Bull (Bubalus bubalis) Spermatozoa

Abstract: Kisspeptin is a powerful regulator of the hypothalamic-pituitary-gonadal axis. It acts through its receptor GPR54 to regulate sexual maturation, oogenesis, spermatogenesis and fertilization. The present research was implemented to evaluate the presence of kisspeptin receptor on various regions of buffalo bull spermatozoa and to decipher its relationship with different motility parameters of the fresh spermatozoa. Standard swim-up protocol was performed on fresh ejaculates from Nili-Ravi buffalo bulls to obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Furthermore, in vitro cell models [ 18 , 21 , 22 ], ex vivo treatments [ 23 , 24 , 25 , 26 ], testis explants [ 26 ], and in vitro co-colture models [ 27 ] have been used to investigate the involvement of the kisspeptin system in male reproduction, revealing a possible physiological role in spermatogenesis progression as well as steroid biosynthesis in several, but not all, of the species tested [ 15 , 16 ] for recent review. In fact, species-specific differences in the expression or localization of Kiss1/Kiss1R were reported in the testis of mammalian and non-mammalian vertebrates [ 16 ], and Kiss1R was detected in the spermatozoa of anuran amphibians, rodents, buffalos, dogs, and humans [ 17 , 25 , 28 , 29 , 30 ]. Kiss1 was recently detected in human seminal plasma with positive association to semen quality parameters [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in vitro cell models [ 18 , 21 , 22 ], ex vivo treatments [ 23 , 24 , 25 , 26 ], testis explants [ 26 ], and in vitro co-colture models [ 27 ] have been used to investigate the involvement of the kisspeptin system in male reproduction, revealing a possible physiological role in spermatogenesis progression as well as steroid biosynthesis in several, but not all, of the species tested [ 15 , 16 ] for recent review. In fact, species-specific differences in the expression or localization of Kiss1/Kiss1R were reported in the testis of mammalian and non-mammalian vertebrates [ 16 ], and Kiss1R was detected in the spermatozoa of anuran amphibians, rodents, buffalos, dogs, and humans [ 17 , 25 , 28 , 29 , 30 ]. Kiss1 was recently detected in human seminal plasma with positive association to semen quality parameters [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Kp-13 and Kp-10 affect intracellular Ca 2+ mobilization in mice and humans, respectively [ 17 , 29 ], with consequences on in vitro fertilization ability in mice [ 17 ]. Effects on progressive sperm motility and transient sperm hyperactivation were reported in humans [ 29 ], but lack of any association between Kiss1R on sperm surface and the acquisition of sperm motility was reported in bulls [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that addition of kisspeptin‐10 in cryodiluent was able to enhance CAT, POD (15 and 20 μmol L −1 ) and GSH (20 μmol L −1 ) content during the cryopreservation process. This improvement of antioxidants by kisspeptin‐10 may also be related to the presence of GPR54 receptors on head, neck and mid‐piece of spermatozoa (Hussain et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, kisspeptin has also been reported to counter the heat-induced oxidative stress in rats by enhancing the reduced glutathione and superoxide dismutase (SOD) levels (Hou et al, 2017). Interestingly, buffalo spermatozoa also possess GPR54 receptors on head, neck and mid-piece (Hussain et al, 2020) thus supporting that kisspeptin-10 may reliably be tested during sperm cryopreservation. Moreover, serum kisspeptin-10 has also been reported to act as a biomarker for better reproductive performance in buffalo bulls (Bhardwaj et al, 2020).…”
mentioning
confidence: 99%
“…The genes responsible for encoding Kp and its receptor are also expressed in the testes of rodents, particularly in Leydig cells, spermatid cells, seminiferous tubules, and testes [52,53] . Recent investigations have examined the effects of Kp on the testes of adult male monkeys, as well as its presence in human and buffalo bull spermatozoa [54,55] . Evidence suggests that Kp may modulate the fertilization capacity of spermatozoa by promoting capacitation, and studies in rats have shown that administration of a Kp antagonist reduced spermatozoa fertilization rates [52] .…”
Section: Kisspeptin's Influence On Gonadal Activitymentioning
confidence: 99%